Normativität und Wertneutralität Grundlegung zu einer Wissenschaftssoziologie der Soziologie - Mevissen, Natalie (Science Studies, 2019)
A part of sociology always wants to distance itself from any interference in the practice, and another part to influence society. In the first case, sociology sees itself as a science that looks at society from the outside. In the second case, she can not evade her affiliation with society. But what do these supposedly contradictory goals mean for sociologists and what does that say about the subject itself? Natalie Mevissen investigates the relationship of sociology to society with the help of hermeneutic interview analyzes and at the same time formulates conditions for a sociology of sociology in theory and methodology. She advocates a change of perspective: away from a problem discourse towards a perspective of the elective affinity of sociology with society.